Machine Learning Models with Neutrosophic Numbers for Network Anomaly Detection and Security Defense Technology - Hussein S Al-Khazraji; Ahmed M. Alkhamees; Humam M Al-Doori; Ahmed A. Metwaly; Mohamed eassa; Ahmed Abdelhafeez; Ahmed S. Salama; Ahmad M. Nagm (Neutrosophic Sets and Systems)
In the dynamic world of cybersecurity, strong solutions are necessary to safeguard intricate network systems. By looking at network anomaly detection and security protection, this study investigates how machine learning (ML) might increase digital infrastructure security. We assess how well critical ML approaches, such as ensemble approaches and supervised learning, identify anomalies and lessen risks. The examination of ML-based systems integration into comprehensive security frameworks places a strong emphasis on real-time monitoring and adaptive responses. Examples from real-world situations highlight how crucial ML is to improving network security. After, we apply different ML models to the real-world dataset. Then we use the single-valued Neutrosophic numbers (SVNNs) methodology to evaluate these ML models and select the best one. We use the multi-criteria decision-making (MCDM) approach to obtain the criteria weights and rank the ML models using the EDAS method. The results show that the random forest model is the best ML model under different evaluation matrices.